Recuerdos, olvidos y desencuentros: Aproximaciones a la subjetividad de los jóvenes andinos - Cánepa, María Angela (1993)
From the concern of a team of young researchers from the Andean South about the identity, the subjective and the affections and experiences of their peers in the region, we can count on a group of interviews about the lives and feelings of a group of young people . We will use this material to build, from a psychosocial perspective, some impressions, not generalizable, circumscribed to the cases interviewed.